2002
DOI: 10.1097/01.lab.0000038554.26102.c6
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a Novel Six-Transmembrane Protein STEAP2, Expressed in Normal and Malignant Prostate

Abstract: SUMMARY:By using subtraction and cDNA array hybridizations, we recently identified an anonymous transcript that was differentially expressed in benign prostate hyperplasia and prostate cancer cell line PC-3. Here, we report the cloning of the full-length cDNA of the gene, designated STEAP2 (six-transmembrane epithelial antigen of the prostate 2). The gene is located at the chromosomal region 7q21 and encodes for a 490 -amino acid protein with six predicted transmembrane domains and is predominantly expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 12 publications
4
85
0
Order By: Relevance
“…STEAP2, which includes ARBS no. 4 in intron 3, has been originally cloned as a STEAP homolog gene that encodes a transmembrane protein expressed in prostate cancer (Porkka et al, 2002). Although androgen responsiveness of STEAP2 was not reported previously, our data showed that it was a novel androgen target gene with a genuine ARBS in intron 3, which was also associated with histone acetylation.…”
Section: Discussionmentioning
confidence: 41%
“…STEAP2, which includes ARBS no. 4 in intron 3, has been originally cloned as a STEAP homolog gene that encodes a transmembrane protein expressed in prostate cancer (Porkka et al, 2002). Although androgen responsiveness of STEAP2 was not reported previously, our data showed that it was a novel androgen target gene with a genuine ARBS in intron 3, which was also associated with histone acetylation.…”
Section: Discussionmentioning
confidence: 41%
“…(27) STAMP1 is highly restricted to prostate for expression and is overexpressed in prostate cancer compared with benign prostate tissue. (28,29) STAMP1 expression is correlated with the presence of functional AR, even though it appears not to be androgen regulated. (28) STAMP2 has a more general tissue distribution.…”
Section: Stamp Familymentioning
confidence: 97%
“…Human tissues express 4 different mRNA transcripts, 3 of them resulting from alternative splicing of the last exon, with estimated sizes of 2.2, 4.0, 4.5, and 6.5 kb (7). However, there is some controversy about the size of the larger transcript, which has also been identified as having 7.5 kb (8). No significant rearrangements of the gene have been detected in LNCaP, PC3, and DU145 prostate cancer cell lines, but 4 sites of base variations were identified in prostate cancer cell lines and in normal prostate tissue.…”
Section: Structural Features Of Steap Genes and Proteinsmentioning
confidence: 99%
“…These cDNA variations originate from a neutral substitution from CTC to CTT with no amino acid change at codon 272 and 3 missense substitutions: TTT to TGT, leading to Phe17Cys; CGA to CAA, leading to Arg456Gln; and ATG to ATT, resulting in Met475Ile. The open reading frame of the STEAP2 gene is located within the third exon and gives rise to a 490-amino acid protein with a predicted molecular weight of 56 kilodaltons (7,8).…”
Section: Structural Features Of Steap Genes and Proteinsmentioning
confidence: 99%